2010
DOI: 10.1021/jp103547s
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Recognition Mechanism for Superoxide Dismutase Presequence Binding to the Mitochondrial Protein Import Receptor Tom20 from Oryza sativa Involves an LRTLA Motif

Abstract: Most mitochondrial proteins are synthesized in the cytosol as precursor and imported into the mitochondria by Tom complexes (translocase of outer membrane complexes). Knowledge of the binding mechanism between precursor and Tom20 in plants is very limited. Here, computational methods are employed to improve our understanding of the interactions between both molecules. To this end, we model mitochondrial superoxide dismutase precursor (pSOD) in complex with Tom20 in Oryza sativa (OsTom20). In a first stage, fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…From these sequences, Tom20 was deduced to bind the consensus sequence fxxff (where f indicates a hydrophobic residue and x indicates any residue) (Okamoto et al, 2002;Obita et al, 2003;Rimmer et al, 2011;Yamamoto et al, 2011). In addition, NMR studies have demonstrated that Tom20 interacts with LRTLA and LRRFV in rice (Oryza sativa) SOD and Arabidopsis threonyl tRNA synthetase, respectively (Zhang et al, 2010). These plant motifs conform to the Tom20 consensus sequence derived from yeast PSs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…From these sequences, Tom20 was deduced to bind the consensus sequence fxxff (where f indicates a hydrophobic residue and x indicates any residue) (Okamoto et al, 2002;Obita et al, 2003;Rimmer et al, 2011;Yamamoto et al, 2011). In addition, NMR studies have demonstrated that Tom20 interacts with LRTLA and LRRFV in rice (Oryza sativa) SOD and Arabidopsis threonyl tRNA synthetase, respectively (Zhang et al, 2010). These plant motifs conform to the Tom20 consensus sequence derived from yeast PSs.…”
Section: Discussionmentioning
confidence: 93%
“…The result showing that pFAg contains only few motifs is rather surprising as many motifs are expected to participate in various steps of the protein import process. Previously, specific motifs were identified, including Tom20 binding sites and mtHsp70 binding sites (Okamoto et al, 2002;Obita et al, 2003;Zhang et al, 2010;Rimmer et al, 2011;Yamamoto et al, 2011). Moreover, the hydrophobic amino acid residues in the N-terminal region are important for efficient protein import into plant MT (Duby et al, 2001;Ambard-Bretteville et al, 2003;(Lee and Whelan, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MM-GBSA approach show the advantage to estimate the binding free energy of the complex[30], [31]. In this study, the implicit generalized Born solvation model was used (igb = 2).…”
Section: Methodsmentioning
confidence: 99%